Design and Development of Solar PV based Power Sprayer for Agricultural Use - Swami, Vinay; Chouhan, Dipesh Kumar; Santra, Piiyabrat; Kothari, Kartik (Annals of Arid Zone, 2016)
Spraying of agricultural chemicals (herbicides, pesticides etc.) is an important field activity to protect crops from different insect, pests and diseases. Conventionally, knapsack sprayers are most commonly used in agricultural crops. Recently, the hand operated knapsack sprayer has been upgraded to power operated sprayer by addition of diesel operated pumps. In this study, a solar PV based sprayer was designed and developed. The developed solar PV sprayer operates both on direct mode and indirect mode. In the direct mode, the sprayer was operated by using electricity generated by 100 Wp polycrystalline PV modules mounted on the sprayer and in the indirect mode it was operated on battery mode using stored electric energy in a deep cycle battery (12 V, 32 Ah). In both modes, a DC motor pump of 60 W was used to generate the required operating pressure to spray the liquid pesticide formulations. Among different types of nozzles available in the market, the best suited one for spraying is the brass nozzle, which requires an operating pressure of about 1.5-2 kg cm-2 to provide a discharge of 900 cm3 min-1 was used in the study. The capacity of the liquid tank in the sprayer was designed with 50 litre capacity for an uninterrupted operation for 2 hours with two nozzles. Analysis of solar radiation data from Jodhpur station showed that the sprayer can be best operated during 9:00 AM to 3:00 PM. Performance of the developed solar PV sprayer on manually drawn vehicle has been tested in field and found satisfactory to spray pesticide in different arid crops. The developed sprayer may be a boon to farmers in Indian farming scenario especially in region where solar energy is available in plenty.